P‐196L: Late‐News Poster: Flickering Behavior in AH‐IPS Liquid Crystal Mode Driven at Low Frequency. Issue 1 (May 2016) - Choi, Jun-Chan; Lee, Dong-Jin; Park, Min-Kyu; Kim, Byeong-Gon; Baek, Ji-Ho; Lee, Joun-Ho; Choi, Hyunchul; Kim, Hak-Rin
Abstract : We investigated the flickering behaviors in AH‐IPS liquid crystal by positive and negative dielectric liquid crystals at the driving frequency of 0.5 Hz. We found various causes of flickering behaviors and proposed suitable methods to solve each case.